Aplicacion de la Teledeteccion para el analisis multitemporal de la regresion glaciar en la Cordillera Blanca - Alva Huayaney, Miguel Ernesto (2009)
Climate changes that affect our planet nowadays, will lead us to approach to what is happening with the mountain glacial of our country, characterized by its fragility. The Cordillera Blanca is one of the most important glacial areas of our country. Most of the monitoring activities have been carried out on the field where many times a lot of obstacles to collect information are found. In this way, Geomatics, by means of Remote Sensing, helps us to conduct with greater ease the monitoring tasks, using satellite images to determine the melting area of the glaciers. For the study, political boundaries of Huaraz and Independencia districts, as well as the use of several satellite images of 1989, 1998 and 2005 have been considered as references, which help us analyse the behaviour of glacial regression in a period of 16 years and forecast such behaviour by 25 years (2014).